2009
DOI: 10.1007/s00484-009-0282-8
|View full text |Cite
|
Sign up to set email alerts
|

Water spray cooling during handling of feedlot cattle

Abstract: Activities involved in receiving or working (e.g., sorting, dehorning, castration, weighing, implanting, etc.) of feedlot cattle cause an increase in body temperature. During hot weather the increased body temperature may disrupt normal behaviors including eating, which can be especially detrimental to the well-being and performance of the animals. Sprinkle cooling of animals has been successfully employed within the pen; however, added moisture to the pens' surface increases odor generation from the pen. A st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The values of AT and RH were markedly outside the reference thermo-neutral zone of 22-35°C for AT and 58-65% for RH, for goats in the tropical regions of the world (Zaytsev et al 1971;Richardson 2002). Similarly, the mean THI value of 87.8, which is an index of thermal load on animals, was above the normal comfort zone of 70-75 (Kadzere et al 2002;Brown-Brandl et al 2009). The result was similar to the findings of Darcan et al (2007), who showed that goats in hot-humid climate suffered heat-stress at AT of 29.2°C and RH of 86.2% (THI of 82.5).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The values of AT and RH were markedly outside the reference thermo-neutral zone of 22-35°C for AT and 58-65% for RH, for goats in the tropical regions of the world (Zaytsev et al 1971;Richardson 2002). Similarly, the mean THI value of 87.8, which is an index of thermal load on animals, was above the normal comfort zone of 70-75 (Kadzere et al 2002;Brown-Brandl et al 2009). The result was similar to the findings of Darcan et al (2007), who showed that goats in hot-humid climate suffered heat-stress at AT of 29.2°C and RH of 86.2% (THI of 82.5).…”
Section: Discussionmentioning
confidence: 98%
“…Panting scores (ranging from 0-5) were recorded for the goats from each group before transportation, 15 min after loading, and during the transportation and post-transportation periods. The panting scores (Table 1) were recorded as earlier described in goats (Darcan et al 2007) and in cattle (Brown-Brandl et al 2009;Gaugban et al 2009). …”
Section: Panting Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the present study, the values of THI was observed under the mild and severe stage during whole experimental period causing heat stress to the goats and the elevated values of heat stress affects the thermoregulatory mechanisms (Kadzere et al 2002, Brown et al 2009. Amelioration of heat stress begins at the cellular level, where there is an interplay of various molecules including activation of heat shock transcription factor 1 that positively correlates to an increased expression of heat shock proteins by binding to promoter region of heat shock elements (HSE) of the HSP genes (Ruell et al 2009).…”
Section: Resultsmentioning
confidence: 53%
“…Wetting cattle is another strategy that feedlot managers may employ to manage high heat loads. Studies utilising overhead water application for cooling feedlot cattle have predominantly focussed on reducing the impact of heat load on physiological responses such as increased body temperature, respiration rate and panting score (Davis et al 2003;Gaughan et al 2004aGaughan et al , 2008aBrown-Brandl et al 2010;Tresoldi et al 2018). Morrison et al (1973) found positive effects of sprinklers on feed intake and weight gain, but not feed efficiency in feedlot cattle.…”
Section: Thermal Comfortmentioning
confidence: 99%